2018
DOI: 10.1055/s-0037-1615812
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Barbed Sutures in Wound Closure Following Knee and Hip Arthroplasty: A Review

Abstract: Lower extremity joint arthroplasty procedures often require a large incision to have an adequate exposure, which subsequently leads to lengthy wounds that may contribute to long closure, anesthesia, and overall operative times. The recently introduced knotless barbed suture may provide better outcomes, faster closure time, and decreased material utilization. Therefore, the aim of this study was to review the impact of barbed sutures on: (1) wound-related complications; (2) closure and operative time; (3) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…[2][3][4] Perioperative advances including the use of tranexamic acid to decrease blood loss, raising the transfusion criteria, and avoiding the use of Foley catheters have further decreased the need for prolonged hospitals stays. [5][6][7] Within the last 10 years, implementation of bundled payment initiatives has placed an emphasis on decreasing the use of costly acute hospital resources as well as postacute rehabilitation and skilled nursing stays. 8 All of these factors have contributed to the rise in same-day and next-day discharge of TKA patients to home.…”
mentioning
confidence: 99%
“…[2][3][4] Perioperative advances including the use of tranexamic acid to decrease blood loss, raising the transfusion criteria, and avoiding the use of Foley catheters have further decreased the need for prolonged hospitals stays. [5][6][7] Within the last 10 years, implementation of bundled payment initiatives has placed an emphasis on decreasing the use of costly acute hospital resources as well as postacute rehabilitation and skilled nursing stays. 8 All of these factors have contributed to the rise in same-day and next-day discharge of TKA patients to home.…”
mentioning
confidence: 99%
“…Following this prerogative, a shorter time spent closing the skin can be of great help. Gililland et al Reported a significantly shorter closure time with subcuticular suture using Stratafix® compared to single suture [ 10 ], as did other authors [ 16 , 19 , 20 ]. Smith et al found that the use of subcuticular suture starting at the center of the wound and directing to the distal and proximal region of the wound made simultaneously by two professionals is a justification for the shorter closure time with subcuticular sutures with Stratafix® versus traditional unabsorbable sutures.…”
Section: Discussionmentioning
confidence: 84%
“…48 As opposed to conventional sutures' reliance on the knot, barbed sutures, with its knotless design, allow shorter wound closure time, hence possibly reduced infection risk and improved cost-effectiveness. 47 In a meta-analysis of studies on barbed versus conventional sutures, Lin et al concluded that the orientation of the barbs in relation to the needle allows barbed sutures to appose tissues. 12,45,46 It was found that although barbed sutures reduced suture time (standardized mean difference (SMD) ¼ À0.95, 95% CI: À1.43, À0.46, p ¼ 0.0001) and operative time (SMD ¼ À0.28, 95% CI: À0.46, À0.10, p ¼ 0.003), its use increased the incidence of complications (OR ¼ 1.43, 95% CI: 1.05, 1.96, p ¼ 0.03), 12,45,46 but in our study, the incidence of both AEs and SAEs is similar in two group and the use of SADBS did not increase the incidence of complications.…”
Section: Safety Resultsmentioning
confidence: 99%
“…Like many other surgeries, TKA requires the use of sutures that reduce operating time, wound closure time, and cost, due to the delicate nature of the knee anatomy. 47 TKA requires fast wound closure to reduce superficial and serious infections. Therefore, the use of barbed sutures without knots may be ideal during TKA due to the speed of wound closure.…”
Section: Discussionmentioning
confidence: 99%